Análise da influência do modelo cinético na modelagem do escoamento trifásico sólido-líquido-gás em golfadas com formação de hidratos - Cavalli, Stella Cristina Pinto (2017)
Hydrate formation is a recurring problem in the oil and gas industry, mainly in offshore pipelines. Low seafloor temperatures and high pressures during production - as well as the availability of water and light gases - favour the formation of hydrate crystals, which are structures in the form of crystalline reticles composed of water molecules that confine molecules of gas. These crystals tend to agglomerate inside the pipes, forming plugs, which can impair or even bring production to a halt. For these reasons hydrates have been extensively studied in the last decades. The model developed by Bassani (2017), at the Multiphase Flow Center (NUEM), evaluates the influence of hydrate formation on the three-phase solid-liquid-gas slug flow - both hydrodynamically and thermally, as well as the influence of the three-phase flow parameters on hydrate formation. The Bassani (2017) model, however, is limited to the use of a kinetic model of hydrate formation, Turner's (2005) model. In this context, the influence of the kinetic model on the formation of hydrates, as well as on the main parameters of solid-liquidgas slug flow, is the focus of the present research project. To achieve this goal, other kinetic models available in the literature were studied, as well as the use availability of each model. The kinetic model of Vysniauskas and Bishnoi (1983) was then selected and implemented into the model developed by Bassani (2017) in order to analyze its influence in the determination of the main flow parameters – velocities of the flow structures, shape and length of the bubble and the length of the unit cell. From the results obtained in the first simulations, it can be observed that the amount of hydrates predicted by the model of Vysniauskas and Bishnoi (1983) is much smaller than the amount predicted by Turner (2005), which has a significant effect on the slug flow parameters. Whereas the Turner (2005) model behaves as a characteristic hydrateforming flow, thus increasing the mean temperature profile of the flow with the velocities and lengths of the structures decreasing from the hydration nucleation onwards, the Vysniauskas and Bishnoi (1983) form such a small quantity of hydrates that the flow behaves like a biphasic flow with heat exchange, but without hydrates - the temperature falls, due to the heat exchange with the external medium, and the superficial velocity of the gas and the length of the bubble increase, due to the gas expansion caused by the pressure drop. A sensitivity analysis of the model to the empirical constants was carried out so that the origin of the discrepancy between the results could be found. Such analysis showed that the constant can completely alter the amount of hydrate formed.